2000
DOI: 10.1021/la000457m
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Total Reflection−Fourier Transform Infrared Study of Methanol Oxidation on Sputtered Pt Film Electrode

Abstract: Methanol oxidation has been investigated at a sputtered Pt film electrode by using in situ Fourier transform infrared spectroscopy with the attenuated total reflection technique, which can identify directly adsorbed species on the electrode surface. Linear CO, bridged CO, formyl species, and formic acid-related species have been clearly identified during the electro-oxidation of methanol in the intact cyclic voltammogram between 0.05 and 1.0 V, where the initial potential is applied at 0.05 or 1.0 V. The formy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
110
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(120 citation statements)
references
References 68 publications
10
110
0
Order By: Relevance
“…Thus, it is indicated that the rapid increase in the MOR current strongly corresponds to the oxidation of the poisoning intermediate CO. Figure 2 shows the ATR-IRAS simultaneously acquired with the LSV for the MOR at the Pt 50 Ru 50 electrode. At the low-potential region less positive than the E onset in Figure 1, strong bipolar-shaped bands and some positive bands are observed at 2050-1700 cm −1 , which can be assigned to the stretching mode of linearly bonded CO (CO L ) at the Pt site (2050 cm −1 ), [23][24][25][26] CO L adsorbed at Ru sites (1940-2000 cm −1 ), [28,29] and the stretching mode of bridge-type CO (CO B , 1700-1900 cm −1 ). [25,26,30] These results indicate that methanol is dehydrogenated to CO ad predominantly while keeping the potential at 0.10 V on the Pt-Ru electrode.…”
Section: Atr-iras At Film Electrodes Of Pt and Pt-ru Alloymentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, it is indicated that the rapid increase in the MOR current strongly corresponds to the oxidation of the poisoning intermediate CO. Figure 2 shows the ATR-IRAS simultaneously acquired with the LSV for the MOR at the Pt 50 Ru 50 electrode. At the low-potential region less positive than the E onset in Figure 1, strong bipolar-shaped bands and some positive bands are observed at 2050-1700 cm −1 , which can be assigned to the stretching mode of linearly bonded CO (CO L ) at the Pt site (2050 cm −1 ), [23][24][25][26] CO L adsorbed at Ru sites (1940-2000 cm −1 ), [28,29] and the stretching mode of bridge-type CO (CO B , 1700-1900 cm −1 ). [25,26,30] These results indicate that methanol is dehydrogenated to CO ad predominantly while keeping the potential at 0.10 V on the Pt-Ru electrode.…”
Section: Atr-iras At Film Electrodes Of Pt and Pt-ru Alloymentioning
confidence: 96%
“…[25][26][27][28] We prepared thin-film Pt or Pt alloy (about 10 nm thick) electrodes on the flat plane of a silicon semicylindrical prism by Ar-sputtering Pt and the second metal targets simultaneously. The resulting alloy composition was determined by energy-dispersive X-ray fluorescence spectroscopy (EDXRF).…”
Section: Atr-iras At Film Electrodes Of Pt and Pt-ru Alloymentioning
confidence: 99%
See 1 more Smart Citation
“…Physical methods, normally referring to vacuum evaporation [10,21,29] and vacuum sputtering [43][44][45], are the first and extensively used approaches. With physical methods, metal films containing island nanoparticles can be directly deposited on the prism.…”
Section: Substrates Fabricationmentioning
confidence: 99%
“…[18,19] However, there is no consensus on the nature of the reactive intermediates in the non-CO pathway. By using in situ IR reflection-absorption spectroscopy or surface-enhanced IR absorption spectroscopy in the Kretschmann (attenuated total reflectance, ATR) configuration, various adsorbates, such as formyl (-HCO) ad , [20] carboxy (-COOH) ad , [20] a dimer of formic acid (HCOOH) 2ad , [21] and formate (HCOO-ad ), [2] were identified as reactive intermediates for methanol electro-oxidation. Similar to CO ad , formate was also argued to be a catalystpoisoning intermediate.…”
Section: Introductionmentioning
confidence: 99%